Struktur dan Fungsi Oru Dia dalam Kebudayaan Suku Yokari - Erlin Novita Idje Djami; Marlina Flassy; Simon Abdi K. Frank (Universitas Cenderawasih, 2021)
Oru dia is a megalithic cultural phenomenon in the form of a circular stone structure, and the stones serve as a seat when customary deliberations are conducted. The existence of this orudia is very interesting to be disclosed about the structure, function and role in the life of Yokari tribe society so that until now still be maintained. Therefore the method used to express about the oru dia by using qualitative approach and data presentation is descriptive. The process of collecting data through interviews, observation, and literature study. While the analysis uses functional structural analysis and hermeneutic data interpretation. The result of this research is the finding of a number of oru dia in kampung which are in Yokari District area. Oru dia-oru dia is made of a number of stones arranged horizontally to form a circle, and in the middle of the circle there is a fireplace. The stones in oru dia are the seats of the Yarona who are the ondowafi messengers who perform their duties and functions based on adat. The existence of this oru dia illustrates the existence of a working structure of traditional tools, and the customary devices will be consulted and cooperate in carrying out the Ondoafi command on the implementation plan of an event or event such as a traditional party, Ondoafi's appointment ceremony as well as in termination of the case. Based on the structure of the oru dia can be known its function is as a place of deliberation, where the coronation of Ondoafi, the place of ratification of the verdict and the place of judging the case. The role of oru dia is as a unifying symbol or a tool that holds the whole of Yokari society, as a symbol of Ondoafi's power, meeting place or customary musyawarah center, place of ratification of a customary decision, Ondoafi's inauguration place witnessed directly by the sun and the univers